Psychosis in Systemic Lupus Erythematosus: Results From an International Inception Cohort Study. Issue 2 (18th January 2019) - Hanly, John G.; Li, Qiuju; Su, Li; Urowitz, Murray B.; Gordon, Caroline; Bae, Sang‐Cheol; Romero‐Diaz, Juanita; Sanchez‐Guerrero, Jorge; Bernatsky, Sasha; Clarke, Ann E.; Wallace, Daniel J.; Isenberg, David A.; et al.
Abstract : Objective: To determine, in a large, multiethnic/multiracial, prospective inception cohort of patients with systemic lupus erythematosus (SLE), the frequency, attribution, clinical, and autoantibody associations with lupus psychosis and the short‐ and long‐term outcomes as assessed by physicians and patients. Methods: Patients were evaluated annually for 19 neuropsychiatric (NP) events including psychosis. Scores on the Systemic Lupus Erythematosus Disease Activity Index 2000, the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index, and the Short Form 36 (SF‐36) were recorded. Time to event and linear regressions were used as appropriate. Results: Of 1, 826 SLE patients, 88.8% were female and 48.8% were Caucasian. The mean ± SD age was 35.1 ± 13.3 years, the mean ± SD disease duration was 5.6 ± 4.2 months, and the mean ± SD follow‐up period was 7.4 ± 4.5 years. There were 31 psychotic events in 28 of 1, 826 patients (1.53%), and most patients had a single event (26 of 28 [93%]). In the majority of patients (20 of 25 [80%]) and events (28 of 31 [90%]), psychosis was attributed to SLE, usually either in the year prior to or within 3 years of SLE diagnosis. Positive associations (hazard ratios [HRs] and 95% confidence intervals [95% CIs]) with lupus psychosis were previous SLE NP events (HR 3.59 [95% CI 1.16–11.14]), male sex (HR 3.0 [95% CI 1.20–7.50]), younger age at SLE diagnosis (per 10 years) (HR 1.45 [95% CI 1.01–2.07]), and African ancestry (HR 4.59 [95% CI 1.79–11.76]). By physician assessment, most psychotic events resolved by the second annual visit following onset, in parallel with an improvement in patient‐reported SF‐36 summary and subscale scores. Conclusion: Psychosis is an infrequent manifestation of NPSLE. Generally, it occurs early after SLE onset and has a significant negative impact on health status. As determined by patient and physician report, the short‐ and long‐term outlooks are good for most patients, although careful follow‐up is required.